Building Lasting Connections: Cultivating Brand loyalty through Relationship and Commitment - Arshad, Farah Noreen (iRASD Journal of Management, 2023)
Because of the cutthroat rivalry that exists in the fashion sector, customers are faced with a bewildering selection of options, which makes it extremely difficult to win and keep their allegiance. Using the literature on relationship marketing as a jumping off point, this study investigates the dynamic link that exists between "brand trust," "customer satisfaction," "brand evaluation," "brand commitment," "brand relationship," and "brand loyalty" in the context of Pakistan's fashion sector. This study conducts an in-depth analysis of 460 answers from important fashion brand customers in the South Punjab province of Pakistan. The data utilised in this investigation was gathered by means of structured surveys that were carried out using the mall intercept methodology. The use of the Structural Equation Modelling (SEM) technique allows for a comprehensive investigation into the ways in which the variables are related to one another on the basis of well-established theoretical premises. The conclusions of this research have important repercussions for marketing executives and brand managers, since they provide such individuals with useful techniques to strengthen client loyalty. These tactics place a strong emphasis on the management of online brand communities and make use of new technology to strengthen market orientation. They are widely regarded as being essential for the cultivation of "brand loyalty" in the fashion industry.